Evaluación de alternativas de transporte para topografías escarpadas en la Comunidad la Virginia, resguardo indígena de Yaquivá, municipio de Inzá Cauca - Rivera Calambas, Herney (Universidad Antonio Nariño, 2022)
For our study, we have focused on the area of Virginia that is part of the Yaquivá indigenous reservation, which, as we have described previously, has a steep topography that is difficult for the population and its economic and social development to access. Our objective is a technical contribution that will allow to evaluate from civil engineering, a transportation alternative that takes into account a point of view of social, environmental and financial aspects. Also, from the review of impacts and costs for this type of steep topographies and slopes with steep slopes, it will allow decisions to be made when determining the construction of a transportation system for this community and for the rest of the communities that share similarities of relief and climate at the national leve